Analysis of Property Tax Revenues Before and During the Covid-19 Pandemic in Sukabumi - Dede Wahidin; Fitri Mareta; Heliani; Retna Wulandari; Widia Khairunnisa (Nusantara Science and Technology Proceedings, 2020)
The problem that occurred during this pandemic, many people were affected by it, including the company so that the community’s income was also reduced to the company. This study aims to find out the Income-tax of property in Sukabumi Regency before the existence of Covid-19 and at the time of Covid-19. The method used in this research is a qualitative method with data collection techniques in the form of direct interviews and data collection directly at the Sukabumi District Revenue Agency office. Based on the results of research conducted that the Property Tax Revenues in District Sukabumi did not always reach the target set in the fiscal year. The target is fulfilled every year because of the receivables in the previous year that he withered in the following years as well as during the pandemic covid-19 even though the target of property tax revenues was lowered and given a stimulus to the taxpayer, in October has exceeded the specified target.